Potensi Kombinasi Pegagan dan Dadap Serep dalam Menurunkan Risiko Nonalcoholic Fatty Liver Disease - Marita Kaniawati; Agus Sulaeman; Elis Susilawati; Nita Selifiana; Naida Kasihtheisya; Widi Syahyudin; Oktaviani Parasitia (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Fructose has long been known as a sugar additive or sweetener, commonly found in soft drinks, pastries and other daily processed foods. An added sugar in large amount in the daily diet will increase the risk of suffering from various diseases due to metabolic disorders including Nonalcoholic Fatty Liver Diseases (NAFLD). The aims of the study is to determine the potential of a combination of ethanol extract of pegagan and dadap serep (EEPDS) to reduce the risk of NAFLD triggered by high fructose consumption. The parameters observed include inflammatory markers (represented by levels of Vascular Cell Adhesion Molecule-1 or VCAM-1), oxidative stress markers (represented by levels of Malondialdehyde or MDA), lipid parameters (represented by Triglycerides) and liver function parameters (represented by levels of Serum Glutamic Oxaloacetic Transaminase or SGOT and Serum Glutamic Pyruvic Transaminase or SGPT). The research method was arranged with Post Test Only Control Group Design using male Wistar rats as test animals for 60 days. This study used 6 treatment groups, namely the normal group (normal diet), induction group (normal diet + 60% fructose), comparison group (normal diet + 60% fructose + curcumin), test group 1 (normal diet + 60% fructose + EEPDS 50:100 mg/kgBW), test group 2 (normal diet + 60% fructose + EEPDS 100:100 mg/kgBW), and test group 3 (normal diet + 60% fructose + EEPDS 100:50 mg/kgBW). The results showed that the combination of ethanol extract of pegagan and dadap serep can reduce the risk of NAFLD, which is characterized by decreased levels of Triglycerides, SGOT, SGPT, MDA and inflammatory markers (VCAM-1). In conclusion, the combination of EEPDS can reduce the risk of NAFLD triggered by high fructose consumption.